A Novel Complication of the Dall-Miles Cable Grip System Mimicking Recurrent Synovial Chondromatosis: A Case Report and Review of the Literature. Issue 4 (October 2016) - Wilson, Jacob; Riff, Andrew J.; Hellman, Michael D.; Sethi, Shenon; Jacobs, Joshua J.; Gitelis, Steven
Abstract : Case: A 25-year-old man with synovial chondromatosis of the hip was treated with a synovectomy through a transtrochanteric approach; the repair was made with use of a Dall-Miles cable. Approximately 13 years later, the patient returned with a massive bursal reaction and a cyst containing "rice bodies." Although the physical examination and imaging were suggestive of recurrent synovial chondromatosis, the bursal reaction actually represented a novel complication of the Dall-Miles system. Conclusion: When a patient who has had prior orthopaedic instrumentation presents with pain and imaging that demonstrates formation of a bursal cyst, a cyst containing rice bodies secondary to bursal irritation by the implant should be considered.